The use of computers as substitute tutors for marketing students - Miriam Catterall; Patrick Ibbotson (Association for Learning Technology, 1995)
The importance of feedback in the learning process is self-evident and well documented (Rowntree, 1987; Brown & Knight, 1994). Students tend to place high value on the feedback they obtain from teaching staff through the assessment process. Assessment can consume as many staff hours as teaching (Gibbs & Jenkins, 1992). With increasing class sizes, teaching staff are encouraged to find ways to reduce the demands the assessment process places on their time. Peer and computer-marked assignments can help in this respect.